Sidikare as Kinship-Based Dispute Resolution of Sasak Muslim within the National and Islamic Law Framework - â Nisfawati Laili Jalilah; Baiq Ratna Mulhimmah; â Syukri; â Parida Angriani (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2025)
The existence of Sidikare as a dispute resolution mechanism within the Sasak Muslim community in Lombok offers a more efficient, affordable, and culturally appropriate alternative to formal litigation. Emphasizing kinship-based mediation and communal dialogue, Sidikare reflects local values while avoiding unnecessary external intervention. This research aims to 1. examine Sidikare as a kinship-based dispute resolution mechanism practiced within the Sasak Muslim community while identifying it in the context of Indonesia’s national legal system, 2. analyze how Sidikare functions as an effective alternative to formal legal mechanisms in resolving family-related conflicts, 3. explore the alignment between Sidikare and Islamic legal principles (ṣulḥ, ‘urf, maṣlaḥah). It employs a normative and sociological legal approach with an empirical juridical methodology. Data were collected through non-participatory observation, unstructured interviews, and documentation in the village of Binneneman Mantang, Central Lombok. The findings reveal that Sidikare is not only effective in addressing communal conflicts but is also perceived by locals as embodying Islamic moral and ethical values, despite its non-formal status. While its legal power remains weak under national customary law politics, Sidikare fulfills the legal needs of the community by offering swift, harmonious, and non-adversarial dispute resolution. The study concludes by recommending the formal recognition and preservation of Sidikare as a complementary Islamic-local institution within Indonesia's plural legal landscape, especially amid modern legal demands.